2015
DOI: 10.1093/femsle/fnv158
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial biosynthetic potential and genetic diversity of endophytic actinomycetes associated with medicinal plants

Abstract: Endophytic actinomycetes are one of the primary groups that share symbiotic relationships with medicinal plants and are key reservoir of biologically active compounds. In this study, six selective medicinal plants were targeted for the first time for endophytic actinomycetes isolation from Gibbon Wild Life Sanctuary, Assam, India, during winter and summer and 76 isolates were obtained. The isolates were found to be prevalent in roots followed by stem and leaves. 16S rRNA gene sequence analysis revealed 16 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 36 publications
1
16
1
Order By: Relevance
“…Analysis of morphological features revealed a high proportion of 111 isolated actinomycetes from the C. cassia host plant. In general, the distribution of isolated endophytic actinomycetes remarkably varies according to the geographic region, plant species, specific plant tissues and isolation media (Gohain et al, 2015;Janso and Carter, 2010;Kaewkla and Franco, 2013;Qin et al, 2009;Salam et al, 2017). For instance, a recent study reported the diversity of endophytic actinomycetes in Dracaena cochinchinensis Lour from 4 distinct provinces of China and Vietnam (Salam et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of morphological features revealed a high proportion of 111 isolated actinomycetes from the C. cassia host plant. In general, the distribution of isolated endophytic actinomycetes remarkably varies according to the geographic region, plant species, specific plant tissues and isolation media (Gohain et al, 2015;Janso and Carter, 2010;Kaewkla and Franco, 2013;Qin et al, 2009;Salam et al, 2017). For instance, a recent study reported the diversity of endophytic actinomycetes in Dracaena cochinchinensis Lour from 4 distinct provinces of China and Vietnam (Salam et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The diversity and bioactivity of endophytic actinomycetes are associated with the genetic background of actinomycetes, plant species and geographic areas (Golinska et al, 2015;Matsumoto and Takahashi, 2017;Qin et al, 2009). Moreover, the distribution of the endophytic actinomycete population also varies according to the different tissues of host plants (Qin et al, 2009;Gohain et al, 2015;Salam et al, 2017). Recently, a number of novels and previously uncultured endophytic actinomycetes with diverse metabolic pathways have been isolated through new isolation approaches and media (Matsumoto and Takahashi, 2017;Qin et al, 2009;Tanvir et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They are the largest possible resource available to obtain novel microorganisms and their valuable natural products 17,18 . Quite a few researchers have reported actinobacteria from the forest ecosystems of Northeast India for the search of natural products endowed with antimicrobial activity [19][20][21][22][23][24][25][26] . However, the literature review reveals that Pobitora Wildlife Sanctuary, located in Assam, India is yet an unexplored forest ecosystem and we had previously reported regarding the bioactivity prospective of its microflora 24 .…”
mentioning
confidence: 99%
“…(5.5 %), and Nocardia (3.6 %) were also isolated. In another study, Gohain and coworkers identified the actinomycetes diversity of 6 medicinal plants collected from Gibbon wildlife sanctuary, Assam, and revealed that A. indica possesses the high Shannon diversity index (1.49) with predominance of Streptomyces species and Streptomyces significantly expressed Polyketide synthase-II (PKS) gene [328]. Endophytic actinomycetes species isolated from A. indica improved plant growth of tomato through the production of siderophores and Indole acetic acid, and inhibited the growth of the pathogen Alternaria alternata that causes blight disease in tomato [324].…”
Section: Defense Against Pathogensmentioning
confidence: 99%